Managing technological innovation in the sports industry: a challenge for retail management - Vrontis, Demetris; Viassone, Milena; Serravalle, Francesca; Christofi, Michael (My University, 2020)
Purpose: The purpose of this paper is twofold: first, to investigate the effects of the digitalization process on the demand and supply side in the sports world through the advent of mobile apps and online services, such as YouTube, which provide free (or almost) real fitness courses; and second, to investigate how technological innovation is managed in the sports sector. Design/methodology/approach: Drawing on a survey research approach, this study collected 150 questionnaires from consumers in the North of Italy. Findings: Based on a descriptive analysis of the data, the findings show that the digital channel becomes significant at an exponential rate and takes on a leading role in today’s era, especially among young people. However, the results also show that the traditional channel of use of the sports service (gyms/fitness centers) is privileged by consumers under the age of 35, even though there is a weak penetration of innovative tools offered by the innovation technology (mobile app and video tutorials on social networks such as YouTube) in the sports sector. Practical implications: The study provides an exhaustive overview of academic literature on technology and innovation management, and provides the contact point between the physical and digital world in the sports sector, and adds a significant scholarly and practical value in the exercise at home perspective of consumers. This research also contributes to the discussion on the competitiveness between the two channels (physical and digital one) in the sports sector, thus giving rise to further research concerning the offer of the type of sports service. Originality/value: This study is among the few that connect the technological advancements and management within the sports industry and provides the ground and theoretical basis for the scholar community to further build on.
Keywords: Mobile technology; New technologies; Social media; Sport; Technology life cycle; Technology management; Young people